Phenotypes and Virulence among Staphylococcus aureus USA100, USA200, USA300, USA400, and USA600 Clonal Lineages - Jessica M. King (American Society for Microbiology, 2016)
ABSTRACT Staphylococcus aureus diseases affect ~500,000 individuals per year in the United States. Worldwide, the USA100, USA200, USA400, and USA600 lineages cause many of the life-threatening S. aureus infections, such as bacteremia, infective endocarditis, pneumonia, toxic shock syndrome, and surgical site infections. However, the virulence mechanisms associated with these clonal lineages, in particular the USA100 and USA600 isolates, have been severely understudied. We investigated the virulence of these strains, in addition to strains in the USA200, USA300, and USA400 types, in well-established in vitro assays and in vivo in the rabbit model of infective endocarditis and sepsis. We show in the infective endocarditis and sepsis model that strains in the USA100 and USA600 lineages cause high lethality and are proficient in causing native valve infective endocarditis. Strains with high cytolytic activity or producing toxic shock syndrome toxin 1 (TSST-1) or staphylococcal enterotoxin C (SEC) caused lethal sepsis, even with low cytolytic activity. Strains in the USA100, USA200, USA400, and USA600 lineages consistently contained genes that encode for the enterotoxin gene cluster proteins, SEC, or TSST-1 and were proficient at causing infective endocarditis, while the USA300 strains lacked these toxins and were deficient in promoting vegetation growth. The USA100, USA200, and USA400 strains in our collection formed strong biofilms in vitro, whereas the USA200 and USA600 strains exhibited increased blood survival. Hence, infective endocarditis and lethal sepsis are multifactorial and not intrinsic to any one individual clonal group, further highlighting the importance of expanding our knowledge of S. aureus pathogenesis to clonal lineages causative of invasive disease. IMPORTANCE S. aureus is the leading cause of infective endocarditis in the developed world, affecting ~40,000 individuals each year in the United States, and the second leading cause of bacteremia (D. R. Murdoch et al., Arch Intern Med 169:463–473, 2009, http://dx.doi.org/10.1001/archinternmed.2008.603 , and H. Wisplinghoff et al., Clin Infect Dis 39:309–317, 2004, http://dx.doi.org/10.1086/421946 ). Even with current medical advances, S. aureus bloodstream infections and infective endocarditis carry mortality rates of 20 to 66% (S. Y. Tong et al., Clin Microbiol Rev 28:603–661, 2015, http://dx.doi.org/10.1128/CMR.00134-14 ). S. aureus lineages associated with human disease worldwide include clonal complex 5 (CC5)/USA100, CC30/USA200, CC8/USA300, CC1/USA400, and CC45/USA600. The CC5/USA100, CC30/USA200, and CC45/USA600 lineages cause invasive disease yet remain poorly characterized. USA300 and cytotoxins are central to most S. aureus virulence studies, and yet, we find evidence that clonal groups are quite heterogeneous in parameters canonically used to measure virulence, including cytotoxicity, biofilm formation, and blood survival, and that the superantigen profile is an important parameter to consider when defining the virulence of S. aureus strains.